Use of Chlorhexidine Solution as an Additional Step in Combination with Conventional and Two or Three Step Adhesive Systems - Miranda, Diogo de Azevedo; Bartocci, Ana Paula (International Journal of Innovative Research in Medical Science, 2018)
Adhesion to dental tissues is one of the main lines of research today, mainly the chemical evolution of adhesives, which allowed the restorative procedures to be performed with greater speed and predictability1. Bonding to dentin is a unique form of tissue engineering in which a matrix of demineralized collagen with residual crystals of hydroxyapatite is used as the basis for the infiltration of resinous monomers, forming the hybrid layer. Most adhesive systems currently available on the market produce good initial bond strength values, allowing the clinician to stick to the dental structure without the need for retentive preparation.